Conceptions of Social Enterprise and Social Entrepreneurship in Europe and the United States: Convergences and Divergences - Defourny, Jacques; Nyssens, Marthe (Journal of social entrepreneurship, 2010)
The concepts of social enterprise and social entrepreneurship are making amazing breakthroughs in EU countries and the United States. Until recently, the debates on both sides of the Atlantic have taken place in parallel trajectories with few connections among them. In the first part of the paper, we describe the European and US historical landscapes in which those concepts took root. In the second part, we analyse how the various conceptualizations have evolved. This analysis paves the way for the third part, in which we highlight the conceptual convergences and divergences among regions as well as within the US and European landscapes.